1991
DOI: 10.1159/000267087
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Concentration in Ocular Tissues and Fluids

Abstract: A simple, precise method for the analysis of selenium (Se) in ocular fluids and tissues using electrothermal atomic absorption spectroscopy is presented. Se concentrations ranged from 0.23 to 0.41 μg/g wet weight in the cornea, iris, lens, and retina. The Se concentration in aqueous humor was 0.008 μg/ml, thus much lower than that of plasma (0.21 μg/ml). The concentration of protein in aqueous humor is about 1.0% of plasma. Since in plasma, Se is entirely bound to proteins, it is likely that the difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, recent studies have shown detrimental effects of selenium levels on human trabecular meshwork (TM) biology in culture 5 6 7 8 9 10 11 12. Selenium is present in aqueous humour13 14 (and thus in direct contact with the TM cells), and it may adversely impact homeostatic measures of TM health in vivo, although this has not yet been shown.…”
mentioning
confidence: 99%
“…Moreover, recent studies have shown detrimental effects of selenium levels on human trabecular meshwork (TM) biology in culture 5 6 7 8 9 10 11 12. Selenium is present in aqueous humour13 14 (and thus in direct contact with the TM cells), and it may adversely impact homeostatic measures of TM health in vivo, although this has not yet been shown.…”
mentioning
confidence: 99%